Pulmonary Endothelial Mechanical Sensing and Signaling, a Story of Focal Adhesions and Integrins in Ventilator Induced Lung Injury - Kelly, Gabriel T.; Faraj, Reem; Zhang, Yao; Maltepe, Emin; Fineman, Jeffrey R.; Black, Stephen M.; Wang, Ting (Frontiers in Physiology, 2019)
Patients with critical illness such as acute lung injury often undergo mechanical ventilation in the intensive care unit. Though lifesaving in many instances, mechanical ventilation often results in ventilator induced lung injury (VILI), characterized by overdistension of lung tissue leading to release of edemagenic agents, which further damage the lung and contribute to the mortality and progression of pulmonary inflammation. The endothelium is particularly sensitive, as VILI associated mechanical stress results in endothelial cytoskeletal rearrangement, stress fiber formation, and integrity loss. At the heart of these changes are integrin tethered focal adhesions (FAs) which participate in mechanosensing, structure, and signaling. Here, we present the known roles of FA proteins including c-Src, talin, FAK, paxillin, vinculin, and integrins in the sensing and response to cyclic stretch and VILI associated stress. Attention is given to how stretch is propagated from the extracellular matrix through integrins to talin and other FA proteins, as well as signaling cascades that include FA proteins, leading to stress fiber formation and other cellular responses. This unifying picture of FAs aids our understanding in an effort to prevent and treat VILI.